Efektivitas Terapi Kombinasi Metformin dan Glimepiride pada Pasien Diabetes Mellitus Tipe 2 : Tinjauan Literatur - Desak Nandini Prameswari Pagedongan; Ketut Widyani Astuti (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disease characterized by hyperglycemia due to insulin resistance, decreased insulin secretion, or a combination of both. The burden of this disease continues to increase globally, making effective, safe, and affordable management an urgent need. One widely used therapeutic strategy is the fixed-dose combination (FDC) of metformin and glimepiride. This combination is considered beneficial because the two drugs complement each other in their mechanisms of action: metformin reduces hepatic glucose production and increases insulin sensitivity, while glimepiride stimulates insulin secretion from pancreatic β-cells. Furthermore, the use of FDC can simplify the treatment regimen, thereby improving patient adherence to long-term therapy. Article searches were conducted through Google Scholar and PubMed with the keywords "((Metformin) AND (Glimepiride)) AND (T2DM) AND (Fixed Dose Combination)", covering publications from 2020–2025 in both English and Indonesian. Of the total articles found, 15 studies met the inclusion criteria for further analysis. The review results showed that the use of metformin–glimepiride FDC was able to reduce HbA1c levels between 0.33% and 2.45%, reducing fasting plasma glucose (FPG) levels by 32–65 mg/dL, and postprandial plasma glucose (PPG) by 38–103 mg/dL. Most studies reported achieving glycemic targets as recommended by the American Diabetes Association (ADA). The most commonly reported side effects were mild hypoglycemia with an incidence of 4.8%–34.5% and gastrointestinal disturbances, but the overall safety profile of this combination was still acceptable. In terms of cost, FDC was considered more economical than the use of separate single drugs. Thus, metformin–glimepiride FDC was proven to be effective, relatively safe, and affordable in glycemic control in T2DM patients, especially in countries with limited resources. These findings support its use as a primary choice in clinical practice.